2023
DOI: 10.1126/scitranslmed.add9990
|View full text |Cite
|
Sign up to set email alerts
|

TREM1 activation of myeloid cells promotes antitumor immunity

Vladislava Juric,
Erin Mayes,
Mikhail Binnewies
et al.

Abstract: Myeloid cells in the tumor microenvironment (TME) can exist in immunosuppressive and immunostimulatory states that impede or promote antitumor immunity, respectively. Blocking suppressive myeloid cells or increasing stimulatory cells to enhance antitumor immune responses is an area of interest for therapeutic intervention. Triggering receptor expressed on myeloid cells-1 (TREM1) is a proinflammatory receptor that amplifies immune responses. TREM1 is expressed on neutrophils, subsets of monocytes and tissue mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Neutrophils are known to undergo apoptosis upon activation. C5a and TREM-1 are established neutrophil-activating agents that were substantially elevated after IRE (Figure E,F). , Consequently, the incubation of NP@NEs with IRE-treated tumor lysate induced neutrophil death and structure disintegration, along with the rapid release of DOX-BSA into the extracellular environment (Figure E,F). Such externalization of DOX-BSA from neutrophils was also observed in vivo under a fluorescence microscope, where the red fluorescent DOX-BSA diffused away from the green-fluorescent neutrophils and penetrated through the tumor mass (Figure F).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are known to undergo apoptosis upon activation. C5a and TREM-1 are established neutrophil-activating agents that were substantially elevated after IRE (Figure E,F). , Consequently, the incubation of NP@NEs with IRE-treated tumor lysate induced neutrophil death and structure disintegration, along with the rapid release of DOX-BSA into the extracellular environment (Figure E,F). Such externalization of DOX-BSA from neutrophils was also observed in vivo under a fluorescence microscope, where the red fluorescent DOX-BSA diffused away from the green-fluorescent neutrophils and penetrated through the tumor mass (Figure F).…”
Section: Discussionmentioning
confidence: 99%
“…The myeloid trigger receptor (TREM) family is an important family of receptors specifically expressed in myeloid cells and involved in many functions of myeloid cells. At the same time, they are also widely expressed on the surface of natural killer cells, B cells, T cells, epithelial cells and endothelial cells, indicating the importance of regulating innate immunity(Juric et al 2023 ). A study has shown that TREM1 is highly expressed in hepatocellular carcinoma tissue and significantly promotes the proliferation and invasion of HCC cells(Duan et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results indicate that even this subset-dependent depletion of Mono/Mac populations may not be prudent in all contexts. To this extent, while anti-CSF1R antibodies have failed to show benefits in clinical trials ( 35 ), other strategies using for example, drugs that modulate specific subsets such as those expressing TREM2 or trigger others by engaging TREM1 may prove more surgical( 36 ). Systematically dissecting the role of individual TAM subtypes will continue to be crucial to deciphering their context-dependent and complex roles in the TME, with a view towards harnessing them for better immunotherapy outcomes.…”
Section: Discussionmentioning
confidence: 99%